Some Aspects of Albanian Seismic Activity in 2022 - Ormeni, Rrapo; Basholli, Fatmir; Daberdini, A.; Sheikhaleslami, Z. (Karshi Multidisciplinary International Scientific Journal, 2024)
Albania is situated in the Alpine-Mediterranean seismic belt, which includes the zone of contact between the lithospheric plates of Africa and Eurasia. The main cause of Albanian seismicity is the collision of the Adria microplate with the Albanian orogeny. This study presents the results of the analysis of parameters of events and some features of the seismicitythat occurred in Albania and its surrounding area during the year 2022. During this year, seismic activity in Albania and its surroundings was characterized by normal seismic activity. In this territory (39.0-43.0N-18.5-21.5E), a total of 3573 earthquakes were recorded, with 7 of themfelt by the population of Albania. These earthquakes ranged in magnitude from 0.2 to 5.5 on the Richter scale, with an average depth of 14 km and a maximum depth of 90 km. Of these, 817 had a magnitude ML >2.0 (Richter), 26 had a magnitude ML > 3.5, and 2 had a magnitude ML > 4.3. The earthquake foci were concentrated mostly along five active fault zones: Durresi -Rodon Cape, Lezha - Ulqin, Thirre - Iballe, Vlore – Elbasan - Diber, and Korca - Oher, as well as the Ionian fault zones. The analysis of focal depths indicates that the seismic activity was mainly generated in the upper and middle crust. An increase in seismic activity was registered on the southern border of Albania in Greek territory. The focal mechanism parameters of a moderate earthquake with magnitude ML4.3 that occurred during 2022 can be used to shed light on the seismotectonics of the Thirre (Fushe Arrez) fault zone and the current stress field. This article analyzes the level of seismicity for the year and some of its main features.